Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

herbdog

  • 3 years ago

Solve: 3(x + 4) − 4(x + 3) = 7x + 16

  • This Question is Closed
  1. UnkleRhaukus
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    expand the brackets

  2. godorovg
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    do it like this 3(x+4)-4(x+3) = 7x+16 = 3x+12 -4x -12=7x +16 get a like terms together like this 3x-4x-7x=16 the 12-12 is zero so no need. -8x=16 get x my itself divide by -8/16 so you have X= -2 hopes this helps

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy